Dinamika perubahan nilai indikator strategis pembangunan pertanian dan transformasi perdesaan - Yofa, Rangga Ditya (Analisis Kebijakan Pertanian, 2024)
Changes in several strategic indicators, including status and ownership of agricultural land and income sources for village residents, characterize rural transformation. This transformation is expected to have a positive impact on the rural economy. This study analyzes the dynamics of rural transformation and formulates anticipatory policies for its negative impacts, with the potential to steer rural development in a positive direction. Panel data from 2022 and Patanas data from 2010/2011 and 2016/2017 from five sample villages were analyzed using descriptive statistics and logit regression. The findings indicate a decrease in the frequency and average area of ​​owned land, an increase in non-owned cultivated land, an increase in the proportion of working in the non-agricultural sector, and an increase in the proportion of non-agricultural income. Agricultural employment factors include land cultivation status, commodities grown, and​​ land ownership. The dynamics of changes in the area and status of land tenure, sources of livelihood, and income structure of rural households do not have significant implications for the decline in rice, corn, and cassava production. Strategic steps to increase household income from agriculture include increasing the planting index, diversifying agriculture, promoting rural-based agricultural industrialization, and attracting young workers to work in villages to strengthen the community of young farmer entrepreneurs.